Nonlinear Finite Element Analysis of Reinforced Concrete Corner Joints Subjected to Opening Moments - Jawad, David A. M.; Assi, Lateef N. (Basrah Journal for Engineering Sciences, 2013)
The study investigates the behaviour of reinforced concrete corner joints under monotonically increasing loads which tend to increase the right angle between the two joint members. The experimental results for two case studies are considered, and the ANSYS computer code is employed to create three-dimensional models for corner joints within the context of the finite element method. The effect of reinforcement details at the corner joint is studied for commonly used detailing systems, and the nonlinear response is traced throughout the entire load range up to failure. The results obtained are generally in good agreement with the experiments, and show that the detailing system has a significant effect on corner joint behaviour, with efficiencies ranging from as low as 54% up to 147%.